Neonatal and Maternal outcomes in GDM and Non GDM Pregnancies - Channashetti , Reshma D; Azaz, Gulnar (Journal of Neonatal Surgery, 2025)
Background: Gestational diabetes mellitus (GDM) is a common pregnancy complication known to impact perinatal outcomes. Among the key neonatal indicators, the Apgar score and birth weight serve as immediate and essential markers of neonatal health. This study aims to evaluate the relationship between GDM and neonatal APGAR scores at 1 and 5 minutes, as well as birth weight, comparing outcomes with those from non-GDM pregnancies. Objectives:To compare APGAR scores and birth weight between neonates born to GDM mothers and those born to non-GDM mothers and assess whether GDM significantly affects these early neonatal parameters. Methods: This hospital-based case-control study analyzed 100 pregnant women (50 GDM, 50 non-GDM) in the Department of Obstetrics and Gynecology from March 2024 to March 2025 to investigate the association between gestational diabetes mellitus (GDM) and maternal-neonatal outcomes. A total of 100 pregnant women were enrolled, with 50 diagnosed with GDM (cases) and 50 without GDM (controls), matched for gestational age. GDM diagnosis was confirmed using the criteria: IADPSG 75g OGTT.Statistical analysis included descriptive statistics, t-tests, chi-square tests, and logistic regression (SPSS v26, p<0.05). Ethical approval and informed consent were obtained. Results: Significant differences were observed between GDM and non-GDM pregnancies. Mothers with GDM showed higher metabolic parameters and increased rates of caesarean deliveries. Neonates born to GDM mothers had greater birth weights but lower APGAR scores compared to controls. Logistic regression confirmed a strong association between GDM and delivery mode Conclusion: This study demonstrates that GDM significantly impacts both maternal and neonatal outcomes, with notable metabolic alterations, increased caesarean deliveries, and affected neonatal health. The findings emphasize the need for vigilant monitoring and management of GDM pregnancies to optimize outcomes. Further research should explore long-term effects and personalized intervention strategies.